Vegetable Butters and Oils as Therapeutically and Cosmetically Active Ingredients for Dermal Use: A Review of Clinical Studies - Poljšak, Nina; Kočevar Glavač, Nina (Frontiers in Pharmacology, 2022)
While the chemical composition of vegetable butters and oils has been studied in detail, there is limited knowledge about their mechanisms of action after application on the skin. To understand their dermal effects better, 27 clinical studies evaluating 17 vegetable oils (almond, argan, avocado, borage, coconut, evening primrose, kukui, marula, mustard, neem, olive, rapeseed, sacha inchi, safflower, shea butter, soybean and sunflower oils) were reviewed in this research. The reviewed studies focused on non-affected skin, infant skin, psoriasis, xerosis, UV-B induced erythema, atopic dermatitis, molluscum contagiosum, tungiasis, scars, striae and striae gravidarum. We conclude that in inflammation-affected skin, vegetable oils with a high content of oleic acid, together with the lack of or a low linoleic acid content, may cause additional structural damage of the stratum corneum, while oils high in linoleic acid and saturated fatty acids may express positive effects. Non-affected skin, in contrast, may not react negatively to oils high in oleic acid. However, the frequency and duration of an oil’s use must be considered an important factor that may accelerate or enhance the negative effects on the skin’s structural integrity.